Extracellular vesicles biogenesis and uptake concepts: a comprehensive guide to studying host–pathogen communication - Sabatke, Bruna (2024)
CAPES (Funding Code 001); Conselho Nacional de Desenvolvimento Científico e Tecnológico, Grant/Award Number: 301719/2016-0, 307314/2018-9 and 404717/2016-0; FIOCRUZ and Basic Parasitology Program AUXPE 2041/2011 (CAPES) Brazil.